Frontier in special needs education and climate change: a thematic review - Mohd Zuri Ghani; Mohamad Nizam Adhaa Kamarudin; Muhamad Fitri Radzuan; Muhammad Amran; Muhammad Amin Mustapa; Mohd Noor Afiq Ramlee; Mohd Hafiz Jaafar; Zahrah Binti Yahya (Springer Science and Business Media LLC, 2026)
Tier 2- Indexed by SCOPUS